Mitigating Man-wildlife Conflict - Identifying Aberrant Predators: a Case Study of the Man-eater of Sonaripur - Rishi, Vinod (Indian Forester, 2005)
One of the problems in wildlife conservation has been the question when to declare an aberrant wild animal dangerous to human life. Another related question is how to identify an aberrant animal out of a number of animals of the same species sharing the same area. In the case study presented here the two questions were addressed to and an aberrant tiger was identified as a potentially dangerous animal much before it became a confirmed man-eater. The case study provides a scope for taking a proactive approach in the case of big cats like the leopard and the tiger for overcoming some of the limitations in mitigation of man-wildlife conflict.